PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DENGAN MODERASI SUPERVISI AKADEMIK Studi pada Guru Kelas SD di UPT Dinas Pendidikan Kecamatan Gunem Kabupaten Rembang (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study was to examine the influence of Competence and Motivation on Academic Performance Supervision Master as a moderating variable in the Elementary School Classroom Teachers in the District Education Office Unit Gunem Rembang . The population in this study were all primary school classroom teacher in the District Education Office Unit Gunem Rembang totaled 116 teachers , primary data was collected using a questionnaire instrument to measure variables using Likert scale . Methods of data using multiple regression analysis . Hypothesis test used in this study is the t-test at a significant level (a ) 0.05 . The study of the effect of variable Kompetesnsi , motivation , the performance of teachers who moderated the academic supervision of primary school teachers in the District Education Office Unit Gunem Rembang , it is concluded that : Teacher Competencies no effect on teacher performance , motivation and a significant positive effect on teacher performance . Academic supervision does not affect the performance of teachers . The test results indicate that the interaction : Supervision academic positively and significantly moderate the effect of teacher competence on teacher performance , academic supervision significantly moderate the effects of motivation on teacher performance . Keywords : Competence , Motivation , academic supervision , teacher performance